Burn by battery, the dangers of portable devices − A case report - Milly S. van de Warenburg; Sophie A. Riesmeijer; Stefan Hummelink; Dietmar J.O. Ulrich; Mariëlle L.A.W. Vehmeijer-Heeman (Burns Open)
Since the introduction of portable electronic devices in the past two decades, reports of burn injuries caused by exploding or leaking batteries have been increasing. We present a case of a 9-year-old patient suffering deep dermal burn wounds due to a power bank malfunctioning, highlighting the potential dangers associated with these devices. This case appears to be part of a growing trend of lithium battery-related accidents, which can lead to a combination of flame, chemical, electrical, and contact burns. Healthcare providers must be prepared to manage the distinctive and often complex nature of battery-related burn injuries, which may differ substantially from traditional thermal burns in terms of depth, severity, and the required treatment protocols.